Analysis of Marketing Strategy and ITS Implications for Consumer Impulse Buying Decisions at Superindo Cikaret Cibinong - Solehudin, Didin; Astuti, Dewi (SEAN Institute, 2025)
Impulse buying behavior significantly impacts retail sales, making it a crucial aspect of consumer purchasing decisions. However, the role of marketing strategies in driving impulse buying behavior remains underexplored, particularly in the context of supermarkets in Indonesia. This study aims to analyze the influence of marketing strategies on consumer impulse buying decisions at Superindo Cikaret Cibinong, focusing on key factors such as pricing, promotions, store layout, and in-store advertising. This research employs a quantitative approach with a descriptive and explanatory research design. Data was collected through a structured survey distributed to Superindo consumers, with the sample size determined using Cochran’s formula. The study applies multiple regression analysis using SPSS software to evaluate the impact of different marketing strategies on impulse buying behavior. The findings reveal that promotional activities and store layout have a significant influence on impulse buying decisions, whereas pricing strategies and in-store advertising have a more moderate effect. The results suggest that well-planned marketing strategies can effectively trigger unplanned purchases, emphasizing the importance of retail environment design in influencing consumer behavior. This study contributes to the existing literature by providing empirical insights into marketing strategies and impulse buying behavior in the Indonesian retail sector. The findings offer practical implications for retail managers, highlighting the need for strategic promotional efforts, optimized store layouts, and engaging advertisements to enhance consumer impulse purchases. Future research could explore additional factors, such as psychological triggers and digital marketing influences, to further understand impulse buying behavior in modern retail environments.